Properties of native and blended oil palm starch with nano-silicon dioxide as binder for particleboard - Norani, Abd Karim; Junidah, Lamaming; Madihan, Yusof; Rokiah, Hashim; Othman, Sulaiman; Salim, Hiziroglu; Wan Noor Aidawati, Wan Nadhari; Kushairi, Mohd Salleh; Taiwo, Owolabi Folahan (Elsevier Science, Ltd., 2020)
The replacement of the synthetic binder like urea formaldehyde and other suitable binder with natural adhesive like starch is very challenging to meet acceptable properties. This study evaluates the physicochemical and properties of both native starch and blended oil palm starch from the mixture of polyvinyl alcohol, boric acid and nano silicon dioxide. The result shows higher crystalline index and enthalpy peak of differentiate scanning calorimetry from blended oil palm starch bonded particleboard in comparison with those bonded with native starch. Morphological changes of native starch after blending process were observed from the scanning electron micrograph. Improvement were seen in both the dimensional stability and internal bond strength. The study shows that blended oil palm starch would be a potential candidate as a green binder in particleboard production.